Factors influencing the growth of e-commerce: The mediating role of digital marketing - Wasiq, Mohammad (Edelweiss Applied Science and Technology, 2025)
The purpose of this research is to determine the reasons that motivate Indian e-commerce marketers to utilize digital marketing and to propose a set of seven such motivators. Digital marketing has played a crucial role in the expansion of the Indian e-commerce sector. The study included a quantitative strategy and exploratory factorial analysis. Levels of relationship between conceptual model constructs and digital marketing’s influence on the growth of e-commerce enterprises were calculated using regression analysis. The growth of e-commerce can be attributed primarily to the increased use of digital marketing, which, in turn, can be attributed to the rise of digital media as a communication medium. The study’s primary consequences lie in the fact that it provides insight into how businesses react to technological innovation, which can then be used to pinpoint the requirements for and the most effective approaches to maintaining this industry’s long-term viability. It is vital to compare these results with those of developed nations to contribute to a global strategy, as the limitations of this study lie in the fact that the hypotheses were evaluated for the Indian e-commerce business environment.